Perlindungan Konsumen Muslim Terhadap Produk Makanan Yang Belum Bersertifikat Halal: Studi Kasus Restoran Sushi Go - Widya Andarestiani; Mutiara Shabreen; Indah Rachmadiny; Aisyah Rahmania; Asep Hakim Zakiran (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2026)
The obligation to consume halal food is a fundamental right of Muslim consumers, guaranteed by Islamic principles and Indonesian positive law. However, in practice, many food business operators still distribute products that have not obtained halal certification, resulting in legal uncertainty and potential material and immaterial losses for Muslim consumers. This study aims to analyze the forms of legal protection available to Muslim consumers regarding food products that are not halal-certified and to examine the responsibility of business actors as well as the role of the government in ensuring halal food compliance in Indonesia, using Sushi Go Restaurant as a case study. This research applies a normative juridical method with a statutory and case approach, supported by library research of primary, secondary, and tertiary legal materials. The findings indicate that legal protection for Muslim consumers has been comprehensively regulated through Law Number 8 of 1999 on Consumer Protection and Law Number 33 of 2014 on Halal Product Assurance. Nevertheless, the implementation of these regulations remains inadequate, particularly in terms of supervision and law enforcement against non-compliant business actors. The absence of halal certification and insufficient disclosure of halal information at Sushi Go Restaurant potentially violates Muslim consumers’ rights to legal certainty and accurate information. Therefore, stronger regulatory enforcement, improved supervision, and increased awareness among business actors and consumers are essential to ensure effective legal protection for Muslim consumers.